A Study on Fractal Geometry & Its Measures and Dimensions: Constructing and developing a theory of noncommutative fractal geometry (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The aim of this chapter is to present necessary background material from the areas of fractal geometry, symbolic dynamics and renewal theory. To that end, we state various well-known results and examples, but also give some new results. With these foundations and those of Chapter 3, we will be able to achieve our overall goal of constructing and developing a theory of noncommutative fractal geometry.